Políticas públicas judiciárias: uma abordagem multidimensional no estudo do acesso à justiça - Richa, Morgana de Almeida (2019)
The low quality of access to justice is represented by bottlenecks that compromise the effectiveness of the system in function. According to the modern conception, access to justice demands the convergence of a just legal order beyond the surpassed vision of mere entry into court. The scope comes to be a qualitative and substantial access to justice, with the commitment of improving citizenship. It is a tendency that accompanies the evolution of the State, which reaches contemporaneousness with permeability of attributions and interpenetrations between the powers. In order to meet the demands of the new framework, the Judiciary enlarges its role, acting as moderating agent of the social conflict. Thus is that, in addition to the typical function, the Judiciary assumes the exercise of public policies as a method to access to justice, varied actions inserted in the multidimensionality of the third Cappelettian renewal wave. The Judiciary begins to formulate and execute public policies, a complex and multidisciplinary dynamic activity, characterized by varied actors and the presence of distinct phases. The programmed actions objective is to efficiently meet the most varied institutional demands, in continuous adaptation of the justice system, far beyond the traditional decision. In the remodeling the State attributions, the Judiciary protagonizes concrete actions, categorized as public judiciary policies, as tools to improve access to justice